Efforts to Increase Public Knowledge about the Utilization of Information Technology through Android Applications Regarding the Ways and Flow of Online Registration for Outpatient Visits in Hospitals Islam Garam Kalianget Sumenep District - Siti Amina Zainal; Nurhasanah; Indra Nurita Octavia; Yusron Haries; Wildan Novel; Joko Prasetyo (Universitas STRADA Indonesia, 2024)
To provide higher quality services to patients, many hospitals adopt information systems. The existence of a precise and accurate information system can reduce the occurrence of unwanted errors so that it can increase more efficient performance and operational speed of the agency. The problem of long waiting times for services is something faced by many hospitals, including the Garam Kalianget Islamic Hospital. By utilizing information technology through an Android application regarding the method and flow of online registration, it can provide benefits to patients, especially in reducing the accumulation of patients in the registration waiting room. The aim of implementing this Community Service activity is to increase public knowledge about the use of information technology through Android applications regarding the method and flow of online registration for outpatient visits at the Garam Kalianget Islamic Hospital. This activity was carried out at the Garam Kalianget Islamic Hospital using a lecture method by the implementation team, attended by patients visiting outpatients at the Garam Kalianget Islamic Hospital. The material presented is evaluated by conducting a question and answer session at the end of the activity, where all questions/quizzes submitted by the implementing team can be answered by the participants. From this activity, the results showed that there was an increase in the highest correct answer of the participants who downloaded the Garam Kalianget Islamic Hospital online application, 30 participants (100%), 28 participants (93%) already knew about the Garam Kalianget Islamic Hospital online application, 28 participants were able to use the Garam Kalianget Islamic Hospital online application ( 93%) and participants know what data is included in filling out participants to register online as many as 28 participants (93%).